PENGARUH PELATIHAN, DEMOGRAFI, DAN KETERAMPILAN TERHADAP PENGGUNAAN SISTEM INFORMASI SUMBER DAYA MANUSIA - Yogatama, Ahmad Nizar (LP2M Institut Teknologi dan Bisnis Asia Malang, 2016)
The purpose of this study was to determine and analyze the effect of training on Human Resources Information System, then investigate and analyze the demographics influence the organization of the Human Resources Information System, the latter is to know and analyze the effect of the organizational skills of the Human Resource Information System. This study uses a quantitative research methods. The population used in this study was 36. The sampling technique in this research is census techniques. Methods of data analysis used in this research is descriptive analysis and Partial Least Square. The study shows that, training and demographics affect the Human Resources Information System. It shows that the Human Resource Information System can be used without special skills how to use the Human Resources Information System.